2003
DOI: 10.1152/ajpcell.00277.2002
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of gap junctions in ovarian granulosa cells: distinct role for connexin43 in early stages of folliculogenesis

Abstract: Ovarian granulosa cells are coupled via gap junctions containing connexin43 (Cx43 or α-1 connexin). In the absence of Cx43, granulosa cells stop growing in an early preantral stage. However, the fact that granulosa cells of mature follicles express multiple connexins complicated interpretation of this finding. The present experiments were designed to clarify the role of Cx43 vs. these other connexins in the earliest stages of folliculogenesis. Dye injection experiments revealed that granulosa cells from Cx43 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 38 publications
3
59
0
1
Order By: Relevance
“…Gap junctions are intercellular channels formed by end-to-end docking of connexons between adjacent cells, each connexon being a cylindrical hexamer of CXs. Among the *20 members of the CX family in mammals [25], CX37 and CX43 are both essential for ovarian follicle development as revealed by analysis of the respective mouse gene knockouts [26,27]. To further characterize the COC-like structures generated from our differentiation protocol, realtime RT-PCR was performed to assess expression of these 2 CXs.…”
Section: Resultsmentioning
confidence: 99%
“…Gap junctions are intercellular channels formed by end-to-end docking of connexons between adjacent cells, each connexon being a cylindrical hexamer of CXs. Among the *20 members of the CX family in mammals [25], CX37 and CX43 are both essential for ovarian follicle development as revealed by analysis of the respective mouse gene knockouts [26,27]. To further characterize the COC-like structures generated from our differentiation protocol, realtime RT-PCR was performed to assess expression of these 2 CXs.…”
Section: Resultsmentioning
confidence: 99%
“…Undocked hemichannels are involved in the release of important signaling molecules, including ATP, NAD + , prostaglandin and glutamate (Stout et al, 2002;Ye et al, 2003;Bruzzone et al, 2001;Cherian et al, 2005;Zhao et al, 2005), suggesting possible roles for gap junction hemichannels in paracrine signaling. Previous studies with Cx43-knockout mice demonstrated an essential role for this connexin in ovarian granulosa cells in supporting folliculogenesis and the development of competent oocytes (Ackert et al, 2001;Gittens et al, 2003;. Although the loss of Cx43 from granulosa cells abolished gap junctional intercellular communication (Gittens et al, 2003;Tong et al, 2006), no evidence has been presented that it is the loss of intercellular channels and not hemichannels, or both, that accounts for the ovarian defects.…”
Section: Discussionmentioning
confidence: 99%
“…Connexin43 (Cx43, encoded by Gja1) is highly expressed in developing follicles, in which it forms the gap junctions coupling granulosa cells (Gittens et al, 2003;Tong et al, 2006). The indispensable role of this connexin during ovarian folliculogenesis has been clearly demonstrated using knockout mice.…”
Section: Introductionmentioning
confidence: 99%
“…Simon et al (1997) showed, that Cx37 deficient mice lack mature Graafian follicles and develop numerous incomplete corpora lutea. Loss of Cx43 on the other hand resulted in an arrest of follicular growth, with most follicles failing to develop multiple granulosa cell layers characteristic of secondary follicles (Ackert et al, 2001;Gittens et al, 2003). This implies that the presence of Cx37 and functional regulation and/or turnover of Cx43 are necessary for ovulation in late folliculogenesis.…”
Section: Discussionmentioning
confidence: 99%